Autoimmunity in Chronic Chagas Disease: A Road of Multiple Pathways to Cardiomyopathy? - De Bona, Elidiana; Lidani, Kárita Cláudia Freitas; Bavia, Lorena; Omidian, Zahra; Gremski, Luiza Helena; Sandri, Thaisa Lucas; Messias Reason, Iara J. de (Frontiers in Immunology, 2018)
Chagas disease (CD), a neglected tropical disease caused by the protozoan Trypanosoma cruzi, affects around 6 million individuals in Latin America. Currently, CD occurs worldwide, becoming a significant public health concern due to its silent aspect and high morbimortality rate. T. cruzi presents different escape strategies which allow its evasion from the host immune system, enabling its persistence and the establishment of chronic infection which leads to the development of chronic Chagas cardiomyopathy (CCC). The potent immune stimuli generated by T. cruzi persistence may result in tissue damage and inflammatory response. In addition, molecular mimicry between parasites molecules and host proteins may result in cross-reaction with self-molecules and consequently in autoimmune features including autoantibodies and autoreactive cells. Although controversial, there is evidence demonstrating a role for autoimmunity in the clinical progression of CCC. Nevertheless, the exact mechanism underlying the generation of an autoimmune response in human CD progression is unknown. In this review, we summarize the recent findings and hypotheses related to the autoimmune mechanisms involved in the development and progression of CCC.